Pola Rantai Pasok Industri Kecil Arang Tempurung, Di Kelurahan Muncul, Tangerang Selatan - Tasya Lianisari; Amnil Wardiah Hasibuan; Riri Sintia Subakti; Sumarni Siregar; Yeni Mardiah; Yayat Sujatna (ITB Ahmad Dahlan Jakarta, 2018)
Number of studies stated that a pattern of short supply chain will reduce the impact of the bullwhip effect, because their interpreting data and information systems that are less integrated in each supply chain can be minimized. Therefore, this research seeks to confirm a pattern of supply chain at charcoal home industry di South Tangerang. Results confirmed that there are still constraints on every supply chain process in the production of the industry, as well as still haven't been able to resolve the existing problems in the supply chain of the production process. Policy recommendation for the industry is the industry needs to have warehouse to store and maintain inventory, both raw material inventory and production inventory.